1995
DOI: 10.1902/jop.1995.66.7.624
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Class II Furcation Involvements in Humans With Bioresorbable and Nonresorbable Guided Tissue Regeneration Barriers. A Randomized Multi‐Center Study

Abstract: In this multi-center study 38 patients with contralateral molar Class II furcation defects were treated with GTR therapy using a bioresorbable matrix barrier (test) and a nonresorbable expanded polytetrafluoroethylene (ePTFE) barrier (control). Following flap elevation, scaling, root planing, and removal of granulation tissue, each device was adjusted to cover the furcation defect. The flaps were repositioned and sutured to complete coverage of the barriers. A second surgical procedure was performed at control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
61
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 16 publications
16
61
1
1
Order By: Relevance
“…However, it is likely that several of the identified furcation defects could be suitable for surgical regenerative procedures. [41][42][43][44] In conclusion, the present radiographie study demonstrated that alveolar bone loss in subjects seeking dental care at the School of Dentistry in Seattle was limited. The PERSSON, HÜLLENDER, LAURELL, PERSSON 355 data indicated that 15% of the subjects had experienced bone loss that might be of clinical concern.…”
Section: Discussionsupporting
confidence: 49%
“…However, it is likely that several of the identified furcation defects could be suitable for surgical regenerative procedures. [41][42][43][44] In conclusion, the present radiographie study demonstrated that alveolar bone loss in subjects seeking dental care at the School of Dentistry in Seattle was limited. The PERSSON, HÜLLENDER, LAURELL, PERSSON 355 data indicated that 15% of the subjects had experienced bone loss that might be of clinical concern.…”
Section: Discussionsupporting
confidence: 49%
“…In this study, the radiographic bone fill was statistically significant compared to baseline in all treatment groups without a significant difference between the test and control groups. In the evaluation of periodontal regeneration, the formation of new periodontal attachment and the formation of new bone have to be separately evaluated, since they seem to be unrelated events [26]. A GTR device (a porous nonchemical cross-linking membrane) was evaluated previously in one-wall intrabony defects in beagle dogs [17].…”
Section: Discussionmentioning
confidence: 99%
“…A polylactic acid barrier was selected as the GTR membrane because the data have demonstrated that this type of barrier is successful in regenerative periodontal therapy [30 Á35] and shows effective clinical results like non-absorbable barriers [36,37]. Polylactic acid barrier is easily adapted to the defect and absorbs by hydrolysis with the rate controlled [34,35].…”
Section: Discussionmentioning
confidence: 99%